Tinjauan Yuridis Status Kewarganegaraan Ganda Menurut Undang-Undang Nomor 12 Tahun 2006 Tentang Kewarganegaraan Republik Indonesia - Marwan Marwan (Universitas 17 Agustus 1945 Semarang, 2024)
Citizens are one of the elements of state formation because the state cannot be formed without citizens. The link between the two is citizenship. Each country has different methods in determining citizenship in the country. Regulations regarding citizenship in Indonesia are listed in Law number 12 of 2006. The Republic of Indonesia uses the principles of ius soli and ius sanguinis in determining citizenship status. Indonesia basically adheres to the principle of single citizenship where one person is only allowed to have one citizenship. However, there are exceptions for children from mixed marriages who have the opportunity to have limited dual citizenship before they are 18 (eighteen) years old or married. This is regulated in article 6 of Law number 12 of 2006 concerning Indonesian citizenship. However, in practice there are still many Indonesian citizens above 18 (eighteen) years old and who do not meet the requirements to obtain limited dual citizenship status. Explained in Article 23 of Law No. 12/2006, the legal consequences that will be accepted if this happens are the loss of Indonesian citizenship status.